Marco Praga e Tatiana Pavlova: due mondi teatrali a confronto (Lebenswelt. Aesthetics and philosophy of experience., 2017)
In the twenties the playwright and stage director Marco Praga became a dramatic critic on the “Illustrazione italiana”. In his incisive production an interesting section is devoted to Tatiana Pavlova, a Russian actress who started performing in Italy in 1923, and gradually introduced a new concept of acting and show.Referring to reviews and pictures, this article investigates two different points of view about theatre, the relationship between text and stage, performance and further components of the show.